Homeschooling and brazilian education under siege in the domestic interior - Ventura , Lidnei (Seven Editora, 2023)
This article discusses homeschooling in Brazil and presents the consequences of its approval in the legal statute of national education for public policies, as well as for the effectiveness of the social function of basic education institutions. It starts with the Critical Theory of Society as a theoretical-methodological framework to analyze the recent approval of homeschooling in the Chamber of Deputies, which is currently being considered by the Federal Senate. Preliminary research results point to the advance of conservative groups on Brazilian public education, besieging educational processes within the bourgeoisie that degrade sociability and make the experience of young people and children unfeasible, whose consequence in the medium and long term is narcissistic and solipsistic formation. This process further aggravates the framework of semi-formation [Halbbildung] instituted by modernity, analyzed by Theodoro Adorno and Walter Benjamin, in relation to the decay of narrative, experience [Erfahrung] and communicability, giving way to the trivialities of experiences [Erlebnis] each increasingly lonely, making a liberating and emancipatory education unfeasible. Thus, homeschooling is conceived as a phenomenon derived from the increasingly accentuated process of interiorization of bourgeois society, which retracts to the private sphere one of the most important achievements of the liberal revolutions: the modern universal public school. This phenomenon deepens the crisis of Brazilian education, suffocated by neoliberal reforms that, in recent decades, have caused a retraction in public investments and made its conditions for expansion and qualification even more precarious. DOI:https://doi.org/10.56238/ptoketheeducati-012